"In the Voices of People Like Me": LGBTQ Coping During Trump's Administration. (February 2022) - Gonzalez, Kirsten A.; Pulice-Farrow, Lex; Abreu, Roberto L.
The present study explored strategies that LGBTQ people used to cope during the U.S. presidential administration of Donald Trump. Coping strategies can buffer the impact of identity-related stigma and decreased psychological well-being, however, little is known about the ongoing coping strategies used by LGBTQ people during Trump's presidential administration. This research addresses this gap in the literature. Participants included 335 LGBTQ individuals who were negatively impacted by the discriminatory policies of the Trump administration. Participants completed an online survey where they discussed the coping strategies they used during the Trump administration. Thematic analysis revealed five coping-related themes, including: (a) Coping Through Connecting With People, (b) Coping Through Self-Care and Self-Preservation Activities, (c) Coping Through Relational Disengagement, (d) Coping Through Activism, and (e) Coping Through Outness Decisions. Our discussion explores how counseling psychologists can work with LGBTQ clients to maximize coping strategies for managing distress during anti-LGBTQ presidential administrations.